1997
DOI: 10.1017/s0950268896007303
|View full text |Cite
|
Sign up to set email alerts
|

Selection of neutralizing antibody escape mutants with type A influenza virus HA-specific polyclonal antisera: possible significance for antigenic drift

Abstract: Ten antisera were produced in rabbits by two or three intravenous injections of inactivated whole influenza type A virions. All contained haemagglutination-inhibition (HI) antibody directed predominantly to an epitope in antigenic site B and, in addition, various amounts of antibodies to an epitope in site A and in site D. The ability of untreated antisera to select neutralization escape mutants was investigated by incubating virus possessing the homologous haemagglutinin with antiseru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…During egg passages, immunogenic pressure results in the emergence of progeny viruses with mutations with an altered antigenic pattern (29). In vitro selection in the presence of monoclonal antibodies and polyclonal (rabbitor mouse-derived) antisera was utilized to identify several antigenic epitopes of the hemagglutinin (8,(30)(31)(32)(33) and the neuraminidase (34). Using polyclonal chicken sera in a cell culture system (10), we recently obtained escape variants whose variations reflect immunoescape beyond the major antigenic HA epitopes affecting several viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…During egg passages, immunogenic pressure results in the emergence of progeny viruses with mutations with an altered antigenic pattern (29). In vitro selection in the presence of monoclonal antibodies and polyclonal (rabbitor mouse-derived) antisera was utilized to identify several antigenic epitopes of the hemagglutinin (8,(30)(31)(32)(33) and the neuraminidase (34). Using polyclonal chicken sera in a cell culture system (10), we recently obtained escape variants whose variations reflect immunoescape beyond the major antigenic HA epitopes affecting several viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, antigenic epitopes in the hemagglutinin (HA) protein were identified by sequencing and structural mapping after generating escape variants in vitro using monoclonal antibodies (21,33,37) or polyclonal (rabbit-or mouse-derived) antiserum (3,23). However, polyclonal antisera from chickens were never used before to generate escape variants, although vaccine escape is a serious problem in influenza virus eradication programs for poultry, especially for HPAIV H5N1 (12).…”
mentioning
confidence: 99%
“…B cells recognize free virions through their external surface molecules, inducing escape mutations in viral surface proteins, such as hemagglutinin and neuraminidase in influenza and GP120 in human immunodeficiency virus (HIV) (8,14,45). CD8…”
mentioning
confidence: 99%